ACCORD guideline for reporting consensus-based methods in biomedical research and clinical practice: a study protocol - Gattrell, WT; Hungin, AP; Price, A; Winchester, CC; Tovey, D; Hughes, EL; van Zuuren, EJ; Goldman, K; Logullo, P; Matheis, R; Harrison, N (BioMed Central, 2022)
Background: Structured, systematic methods to formulate consensus recommendations, such as the Delphi process or Nominal Group Technique, among others, provide the opportunity to harness the knowledge of experts to support clinical decision making in areas of uncertainty. They are widely used in biomedical research, in particular where disease characteristics or resource limitations mean that high-quality evidence generation is difficult. However, poor reporting of methods used to reach a consensus – for example, not clearly explaining the definition of consensus, or not stating how consensus group panellists were selected – can potentially undermine confidence in this type of research and hinder reproducibility. Our objective is therefore to systematically develop a reporting guideline to help the biomedical research and clinical practice community describe the methods or techniques used to reach consensus in a complete, transparent, and consistent manner.